Alelopatia em Pteridium arachnoideum (Kaulf.) Maxon. (Dennstaedtiaceae) - Jatoba, Luciana de Jesus (2016)
Pteridium plants are ferns (monilopytes) distributed all around the globe. These plants are considered problem species as they invade recently abandoned or burned areas, and areas under anthropogenic impacts. In Brazil, Pteridium arachnoideum (Kaulf.) Maxon. has become an important problem species at the Cerrado (Tropical Savanna) and Atlantic Forest biomes. To understand the mechanisms underlying invasive plants success are one of the greatest challenges of the last decades. Among the interaction that can influence this success, we find allelopathy. However, untill now we have few evidences for this phenomenon on these plants, especially from the isolation and indentification of secondary metabolites with activities related to allelopathy. Therefore, the present work aimed to evaluate the allelopathy role by direct phytotoxicity and abiotic changes in Pteridium arachnoideum (Kaulf.) Maxon. dominance in the areas it invades. To do so, the bioguided phytochemical study of this plant tissues and litter was performed, as well as the evaluation of the phytotoxic activity of phenolic compounds present in its litter and of its isolated and identified secondary metabolite against the early development of sesame, verifying the presence of this compound in the soil, its quantification, and evaluation of its interactions with physical and chemical soil characteristics. The phytochemical study led to the isolation and identification of a majoritarian compound in the plants green fronds and litter, the proanthocianidin selligueian A. This is the first time this compound is described for P. arachnoideum, as well as for the Dennstaediaceae family. Selligueain A showed phytotoxic activity against wheat coleoptiles elongation, with inhibitory activity over 71%, and IC50 of 0.69 mM. The poliphenols enriched fraction extracted from P. arachnoideum litter exert inhibitory activity against the early development of bioindicators species, native and invasive species of the Cerrado biome, specially over the development of these seedlings roots, besides activity against the metaxylem cells of sesame, and against chlorophyll content of sesame and the native weed Setaria parviflora. The allelopathic potential of the main poliphenolic compound of P. arachnoideum, selligueain A, was also evaluated against the early growth of sesame seedlings, promoting root and shoot growth in all the concentrations tested. Sesame seedlings grown in the presence of selligueain A showed smaller metaxylem cells when compared to the control, in the concentrations of 0.3 mM e 1 mM, with 50.82% inhibition in the greatest concentration and IC50 value of 0.98 mM. There was no activity of selligueain A against chlorophyll content of these seedlings. Analyses of extracts of soil collect under a P. arachnoideum patches pointed to the presence of selligueain A as major compound in soil solution, and, therefore, as a putative allelochemical produced by this plant. The concentration observed for this compound in the soil raged between 0.02 and 0.65 mM. According to allelopathic potential results, this concentration rage is sufficient to act over cooccurring plant species, promoting P. arachnoideum dominance. The presence of P. arachnoideum in Cerrado areas alters the chemical conditions of the soil, especially regarding N and Al, when compared to the presence of U. decumbens. Additionally, Al concentration is correlated to litter mass and to selligueain A concentration at the sites sampled. These results corroborates the hypothesis of allelopathy as a dominance mechanism of this plant in the areas where it occurs, with the first report of an allelochemical for a Pteridium species, by direct phytotoxic activity as well as by controlling Al concentration at those areas.